Microbiome characterization of a pre-Hispanic man from Zimapán, Mexico: Insights into ancient gut microbial communities - Santiago Rosas-Plaza; Luisa Mainou; Gabriela Delgado; Rosario Morales; Ariana Aguilar-Romero; Ana E. Escalante; Rene Cerritos (PLoS ONE, 2025)
The research of microbiome derived from mummified human remains, coprolites and paleofeces has gained significant interest over several decades, aiming to elucidate the evolution of microbial interactions and shed light on the lifestyles of past populations. In this study, we analyzed the gut microbiome of a pre-Hispanic male individual referred to as the Zimapán man, dated to 936 BP, discovered on the border between Mesoamerica and Aridoamerica. Employing high-throughput 16S rRNA gene sequencing on both the paleofeces and mummified intestinal tissue, we conducted a comprehensive characterization of the Zimapán man’s gut microbiome. The bacterial community was described, and a weighted UniFrac-based principal coordinates analysis (PCoA) was performed. The multivariate analysis incorporated microbiome samples from diverse environments, such as soils, compost, and both contemporary and ancient human gut microbiota. The analysis revealed bacterial groups associated with the human microbiome, including families such as Peptostreptococcaceae, Clostridiaceae, Enterobacteriaceae, and Enterococcaceae. Notably, a high abundance of the Clostridiaceae group was found, similar to those discovered in the intestinal tissue of mummies from other geographic regions. Additionally, unique groups such as Romboutsia hominis, exclusively isolated from human intestines and not previously reported in ancient human microbiomes, were identified. Furthermore, our analysis demonstrated that the bacterial composition did not resemble soil and compost environments. This initial characterization successfully achieved the goal of identifying bacterial groups of the gut microbiome in the Zimapán samples. Consequently, this study contributes to the ongoing expansion of knowledge regarding ancient microbiomes across diverse temporal, historical, geographical, and environmental contexts.